Leaf fitness and stress response after the application of contaminated soil dust particulate matter - Lhotská, Marie; Zemanová, Veronika; Pavlík, Milan; Pavlíková, Daniela; Hnilička, František; Popov, Marek (Scientific reports, 2022)
In this study, we observed the effect of the application of soil dust enriched with risk elements (Cd, Pb, As and Zn) to leaf surfaces of lettuce (Lactuca sativa var. capitata) while it was grown under hydroponic conditions. This study aimed to determine how low soil dust particulate matter (PM) doses affected the activity of or damaged the photosynthetic apparatus and how the uptake of risk elements was associated with both epigenetic changes (5-methylcytosine content, i.e., 5mC) and stress metabolism. During the study, we obtained many results pertaining to risk element contents and biochemical (total phenolic content (TPC), malondialdehyde (MDA) content and the amount of free amino acids (AAs)) and physiological (photosynthesis parameters: net photosynthetic rate, transpiration rate, intercellular CO2 concentration, stomatal conductance, instantaneous water-use efficiency, maximum quantum yield of PSII, chlorophyll and carotenoid contents, and leaf water potential (WP)) plant features. The results showed an increase in MDA and 5mC. However, the transpiration rate, WP and free AAs decreased. In conclusion, contamination by very low doses of soil dust PM had no direct or significant effect on plant fitness, as shown by the TPC and 5mC content, which indicates that plants can overcome the oxidative stress caused by the accumulation of risk elements. From the above, we propose the use of epigenetic changes as biomarkers of potential changes in the activation of plant metabolism under stress caused by environmental pollution.
Keywords: Lactuca; pevné částice; rostliny; chlorofyl; voda; Plant Leaves; prach; Water; Plants; půda; fotosyntéza; znečištění životního prostředí; salát (hlávkový); Environmental Pollution; Photosynthesis; Chlorophyll; Particulate Matter; listy rostlin; Soil; Dust